2022
DOI: 10.29244/jitkt.v14i1.39648
|View full text |Cite
|
Sign up to set email alerts
|

KEBIASAAN MAKAN DAN FREKUENSI KEMUNCULAN HIU PAUS (Rhincodon typus) DI PERAIRAN KWATISORE DALAM HAK ULAYAT LAUT KAMPUNG AKUDIOMI DI TAMAN NASIONAL TELUK CENDERAWASIH

Abstract: Hiu paus (Rhincodon typus) adalah ikan terbesar di dunia yang sangat berpotensi dalam bidang wisata, namun potensi ancamannya juga tinggi jika tidak dikelola dengan baik. Perairan Kwatisore merupakan salah satu habitat hiu paus di Indonesia yang terlihat sering muncul. Hal tersebut menjadi fenomena yang unik karena hiu paus muncul setiap hari dan sepanjang tahun, sehingga berpeluang untuk pengembangan wisata. Penelitian ini bertujuan untuk mengkaji karakteristik pola makan hiu paus dan agregasinya, terutama to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
0
1
Order By: Relevance
“…The whale sharks that were documented to have been landed in Pangandaran Bay over the last two decades give important insight into both the whale sharks and the artisanal fishery communities. Contrary to Maruanaya [40], who reported that whale sharks were only present in Pangandaran in the months of August and September, the records suggest their year-round presence. The whale sharks that were landed in Pangandaran Bay were between 3.5 and 15 m in length, averaging 6.9 m, and the larger sample averaged 6.7 m. This is markedly larger than the mean of 4.3 ± 1.0 m (range 3-7 m) of live whale sharks in Indonesian waters, as reported by Himawan et al [41].…”
Section: Whale Shark Landings In Pangandaran Bay and Javacontrasting
confidence: 99%
“…The whale sharks that were documented to have been landed in Pangandaran Bay over the last two decades give important insight into both the whale sharks and the artisanal fishery communities. Contrary to Maruanaya [40], who reported that whale sharks were only present in Pangandaran in the months of August and September, the records suggest their year-round presence. The whale sharks that were landed in Pangandaran Bay were between 3.5 and 15 m in length, averaging 6.9 m, and the larger sample averaged 6.7 m. This is markedly larger than the mean of 4.3 ± 1.0 m (range 3-7 m) of live whale sharks in Indonesian waters, as reported by Himawan et al [41].…”
Section: Whale Shark Landings In Pangandaran Bay and Javacontrasting
confidence: 99%
“…In several countries with regular seasonal constellation patterns, whale shark ecotourism areas have developed and attracted many tourists, such as in Oslob, Philippines (Craven, 2012), Isla Holbox, Mexico (Ziegler et al, 2012) and Ningaloo Reef, Australia (Mau, 2008). In Indonesia, several locations have been developed into whale shark tourism destinations such as Kwatisore Waters, Cendrawasih Bay National Park, Papua (Maruanaya et al, 2022), Bentar Beach Waters, Probolinggo (Kapinangasih et al, 2022), Labuhan Jambu Waters in Saleh Bay, Sumbawa, West Nusa Tenggara and Botubarani Waters, Gorontalo (Djunaidi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%